Sheet

By integrating a polymer with specific units into fine fibrous cellulose sheets, the sheets achieve both high transparency and water resistance, along with improved mechanical strength, addressing the limitations of existing materials.

JP7602387B2Active Publication Date: 2024-12-18OJI HLDG CORP
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2021016738
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-02-04
Publication Date
2024-12-18
Estimated Expiration
2036-07-14

AI Technical Summary

Technical Problem

Existing sheets and molded articles containing fine fibrous cellulose often lack both high transparency and water resistance, necessitating a solution that enhances these properties without compromising other performance characteristics.

Method used

Incorporating a polymer containing specific structural units derived from a polyol and a nitrogen-containing compound into fine fibrous cellulose sheets, with optional introduction of ionic functional groups like phosphoric acid groups, to achieve transparency, water resistance, and improved mechanical properties.

Benefits of technology

The resulting sheets exhibit high transparency (haze of 30 or less), low water absorption (5000% or less), and enhanced mechanical strength (tensile modulus of 2.0 GPa or more and tensile strength of 40 MPa or more), while minimizing yellowness and maintaining structural integrity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007602387000005
    Figure 0007602387000005
  • Figure 0007602387000006
    Figure 0007602387000006
  • Figure 0007602387000001
    Figure 0007602387000001
Patent Text Reader

Abstract

To provide a fine fibrous cellulose-containing sheet having both high transparency and water resistance.SOLUTION: A sheet contains fibrous cellulose with a fiber width of 1000 nm or less, and a polymer containing a polyol-derived unit and a nitrogen-containing compound-derived unit, the sheet having a haze of 30 or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a sheet. In particular, the present invention relates to a sheet comprising fine fibrous cellulose. [Background technology]

[0002] In recent years, materials using renewable natural fibers have been attracting attention due to the need to replace petroleum resources and growing environmental awareness. Among natural fibers, fibrous cellulose with a fiber diameter of 10 μm to 50 μm, especially fibrous cellulose (pulp) derived from wood, has been widely used mainly for paper products.

[0003] As fibrous cellulose, fine fibrous cellulose with a fiber diameter of 1 μm or less is also known. In addition, sheets made of such fine fibrous cellulose, and composite sheets and molded articles containing a fine fibrous cellulose-containing sheet and a resin have been developed. It is known that in sheets and molded articles containing fine fibrous cellulose, the number of contact points between fibers is significantly increased, and therefore the tensile strength is greatly improved.

[0004] Patent Document 1 discloses a polyurethane resin composition obtained by micronizing cellulose in a polyol and then reacting it with a polyisocyanate. It is proposed to form a high-strength molded body from the obtained polyurethane resin composition. Patent Document 2 discloses a coating agent containing fine fibrous cellulose. In Patent Document 2, a coating agent containing water-soluble carbodiimide and alkoxysilane in addition to fine fibrous cellulose is obtained, and such a coating agent is applied to the surface of a molded body to form a coating layer. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] JP 2013-194162 A [Patent Document 2] JP 2010-184999 A Summary of the Invention [Problem to be solved by the invention]

[0006] In a sheet or molded article containing fine fibrous cellulose, high transparency and water resistance may be required depending on the application. Therefore, the present inventors have conducted studies with the aim of providing a fine fibrous cellulose-containing sheet having both high transparency and water resistance. [Means for solving the problem]

[0007] As a result of intensive research to solve the above problems, the inventors have discovered that a sheet having both high transparency and water resistance can be obtained by incorporating a polymer containing a specific structural unit into a fine fibrous cellulose-containing sheet. Specifically, the present invention has the following configuration.

[0008] [1] A sheet containing fibrous cellulose having a fiber width of 1000 nm or less and a polymer containing a unit derived from a polyol and a unit derived from a nitrogen-containing compound, the sheet having a haze of 30 or less. [2] The sheet according to [1], having a water absorption rate of 5000% or less. [3] The sheet according to [1] or [2], having a total light transmittance of 86% or more. [4] The sheet according to any one of [1] to [3], wherein the fibrous cellulose has a phosphate group or a substituent derived from a phosphate group. [5] The sheet according to any one of [1] to [4], wherein the unit derived from a nitrogen-containing compound is a unit derived from at least one compound selected from an isocyanate compound and a carbodiimide compound. [6] The sheet according to any one of [1] to [5], wherein the unit derived from a polyol is a unit derived from a diol. [7] The sheet according to any one of [1] to [6], having a tensile modulus of elasticity of 2.0 GPa or more. [8] The sheet according to any one of [1] to [7], having a tensile strength of 40 MPa or more. [9] The yellowness of the sheet measured in accordance with JIS K 7373 is expressed as YI 1 The yellowness index after drying the sheet in a vacuum at 200°C for 4 hours was calculated as YI. 2 In this case, YI 2 -YI 1 The sheet according to any one of [1] to [8], wherein the value is 50 or less.

[10] The sheet according to any one of [1] to [9], wherein the content of the polymer containing a unit derived from a polyol and a unit derived from a nitrogen-containing compound is 15 mass % or more and 85 mass % or less based on the total mass of the sheet. Effect of the Invention

[0009] According to the present invention, a sheet having both high transparency and water resistance can be obtained. [Brief description of the drawings]

[0010] [Figure 1] FIG. 1 is a graph showing the relationship between the amount of NaOH dropped onto the fiber raw material and the electrical conductivity. [Diagram 2] FIG. 2 is a graph showing the relationship between the amount of NaOH dropped onto a fiber raw material having a carboxyl group and electrical conductivity. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] The present invention will be described in detail below. The following description of the constituent elements may be based on representative embodiments or specific examples, but the present invention is not limited to such embodiments. In this specification, the term "unit" refers to a repeating unit (monomer unit) that constitutes a polymer.

[0012] (Sheet) The present invention relates to a sheet containing fibrous cellulose having a fiber width of 1000 nm or less and a polymer containing a unit derived from a polyol and a unit derived from a nitrogen-containing compound. Here, the haze of the sheet is 30 or less. Since the sheet of the present invention is a sheet containing fibrous cellulose having a fiber width of 1000 nm or less (hereinafter also referred to as fine fibrous cellulose), it can also be called a fine fibrous cellulose-containing sheet. Since the sheet of the present invention has the above-mentioned configuration, it has high transparency. In addition, the sheet of the present invention has low water absorption and high water resistance.

[0013] The haze of the sheet of the present invention may be 30 or less, preferably 20 or less, more preferably 10 or less, even more preferably 5 or less, and particularly preferably 3 or less. The haze of the sheet may be 0%. The present invention is characterized in that a highly transparent sheet is obtained. Here, the haze of the sheet is a value measured using a haze meter (HM-150, manufactured by Murakami Color Research Laboratory Co., Ltd.) in accordance with JIS K 7136.

[0014] The total light transmittance of the sheet of the present invention is preferably 86% or more, more preferably 89% or more, even more preferably 90% or more, and particularly preferably 91% or more. Here, the total light transmittance of the sheet is a value measured using a haze meter (HM-150, manufactured by Murakami Color Research Laboratory Co., Ltd.) in accordance with JIS K 7136. In the present invention, the type of haze and total light transmittance of the sheet can be controlled by appropriately selecting the fiber diameter and production method of the fine fibrous cellulose, respectively.

[0015] The water absorption rate of the sheet of the present invention is preferably 5000% or less, more preferably 3000% or less, even more preferably 1000% or less, even more preferably 700% or less, particularly preferably 500% or less, and most preferably 400% or less. By setting the water absorption rate of the sheet within the above range, the water resistance of the sheet can be improved. Here, the water absorption rate of the sheet can be calculated by the following formula. Water absorption rate (%) = 100 × (wet weight - conditioned weight) / conditioned weight In the above formula, the conditioned weight is the weight of a sheet cut to a given size, measured after conditioning the sheet for 24 hours under conditions of 23°C and 50% relative humidity. The wet weight is the weight of a sheet cut to a given size, immersed in ion-exchanged water for 24 hours, and then wiped off excess water remaining on the surface. In the present invention, the water absorption rate of the sheet is an index for evaluating the water resistance of the sheet, and a low water absorption rate means a high water resistance. The water resistance of the sheet can be controlled, for example, by the type and blending ratio of the polymer added.

[0016] The tensile strength of the sheet of the present invention may be 15 MPa or more, preferably 20 MPa or more, more preferably 30 MPa or more, even more preferably 40 MPa or more, and particularly preferably 50 MPa or more. The upper limit of the tensile strength of the sheet is not particularly limited, but may be, for example, 500 MPa or less. Here, the tensile strength of the sheet is a value measured using a tensile tester Tensilon (manufactured by A&D Co., Ltd.) in accordance with JIS P 8113. When measuring the tensile strength, a test piece is prepared by conditioning the test piece at 23°C and a relative humidity of 50% for 24 hours, and the measurement is performed under conditions of 23°C and a relative humidity of 50%. In the present invention, the tensile strength can be easily adjusted to within the above range by appropriately selecting the type of functional group to be introduced into the fine fibrous cellulose and the fiber diameter of the fine fibrous cellulose, and appropriately selecting the types and blending ratios of the fine fibrous cellulose and the polymer.

[0017] The tensile modulus of the sheet of the present invention is preferably 1.5 GPa or more, more preferably 2.0 GPa or more, even more preferably 3.0 GPa or more, and particularly preferably 4.0 GPa or more. The upper limit of the tensile modulus of the sheet is not particularly limited, but can be, for example, 50 GPa or less. Here, the tensile modulus of the sheet is a value measured using a tensile tester Tensilon (manufactured by A&D Co., Ltd.) in accordance with JIS P 8113. When measuring the tensile modulus, a test piece is prepared by conditioning the test piece at 23°C and a relative humidity of 50% for 24 hours, and the measurement is performed under conditions of 23°C and a relative humidity of 50%. In the present invention, the tensile modulus can be easily adjusted to within the above range by appropriately selecting the type of functional group to be introduced into the fine fibrous cellulose and the fiber diameter of the fine fibrous cellulose, and appropriately selecting the types and blending ratios of the fine fibrous cellulose and the polymer, respectively.

[0018] Since the sheet of the present invention has the tensile strength and tensile modulus within the above ranges, it can exhibit excellent tensile durability. The sheet of the present invention is also characterized by such high tensile strength.

[0019] The yellowness of the sheet of the present invention is preferably 5.0 or less, more preferably 3.0 or less, even more preferably 2.0 or less, and particularly preferably 1.5 or less. Here, the yellowness of the sheet is the yellowness of the sheet obtained in the sheet forming process, and is the yellowness of the sheet before the heat drying process described below. The yellowness of the sheet is a value measured in accordance with JIS K 7373. As a measuring instrument, for example, Colour Cute i (manufactured by Suga Test Instruments Co., Ltd.) can be mentioned.

[0020] The yellowness of the sheet of the present invention after vacuum drying at 200° C. for 4 hours is preferably 60 or less, more preferably 50 or less, even more preferably 40 or less, even more preferably 30 or less, particularly preferably 25 or less, and most preferably 20 or less. The yellowness of the sheet after vacuum drying at 200° C. for 4 hours is also a value measured in accordance with JIS K 7373 as above.

[0021] As described above, the yellowness of the sheet before the heat drying process is defined as YI. 1 The yellowness of the sheet after vacuum drying at 200°C for 4 hours is expressed as YI 2 In this case, YI 2 -YI 1 The value of YI (ΔYI) is preferably 55 or less, more preferably 50 or less, even more preferably 40 or less, even more preferably 30 or less, particularly preferably 25 or less, and most preferably 20 or less. 2 -YI 1 By setting the value (ΔYI) within the above range, yellowing of the sheet can be suppressed, and in particular, yellowing due to heat drying can be effectively suppressed. In the present invention, the value of ΔYI can be easily adjusted to be within the above range by appropriately selecting the type of functional group to be introduced into the fine fibrous cellulose and the type of polymer, respectively.

[0022] The thickness of the sheet of the present invention is not particularly limited, but is preferably 5 μm or more, more preferably 10 μm or more, and even more preferably 20 μm or more. The upper limit of the thickness of the sheet is not particularly limited, but can be, for example, 1000 μm or less. The thickness of the sheet can be measured with a stylus thickness gauge (Millitron 1202D, manufactured by Mahl Co., Ltd.).

[0023] The basis weight of the sheet of the present invention is 10 g / m 2 It is preferable that the thickness is 20 g / m or more. 2 More preferably, it is 30 g / m or more. 2It is more preferable that the basis weight of the sheet is 100 g / m or more. 2 It is preferable that the thickness is less than 80 g / m 2 It is more preferable that the basis weight of the sheet is not more than 1000 g / m2.

[0024] (fibrous cellulose) The sheet of the present invention contains fibrous cellulose having a fiber width of 1000 nm or less. The fine fibrous cellulose is preferably a fiber having an ionic functional group, and in this case, the ionic functional group is preferably an anionic functional group (hereinafter also referred to as an anionic group). The anionic group is preferably at least one selected from, for example, a phosphate group or a substituent derived from a phosphate group (sometimes simply referred to as a phosphate group), a carboxyl group or a substituent derived from a carboxyl group (sometimes simply referred to as a carboxyl group), and a sulfone group or a substituent derived from a sulfone group (sometimes simply referred to as a sulfone group), more preferably at least one selected from a phosphate group and a carboxyl group, and particularly preferably a phosphate group. In this specification, the fibrous cellulose having a phosphate group is sometimes referred to as phosphorylated fine fibrous cellulose.

[0025] The content of the fine fibrous cellulose is preferably 10% by mass or more, more preferably 20% by mass or more, and even more preferably 35% by mass or more, based on the total mass of the sheet. The content of the fine fibrous cellulose is preferably 85% by mass or less, and more preferably 90% by mass or less. By setting the content of the fine fibrous cellulose within the above range, the tensile strength of the sheet can be more effectively increased.

[0026] The fibrous cellulose raw material for obtaining fine fibrous cellulose is not particularly limited, but it is preferable to use pulp because it is easily available and inexpensive. Examples of pulp include wood pulp, non-wood pulp, and deinked pulp. Examples of wood pulp include chemical pulps such as hardwood kraft pulp (LBKP), softwood kraft pulp (NBKP), sulfite pulp (SP), dissolving pulp (DP), soda pulp (AP), unbleached kraft pulp (UKP), and oxygen bleached kraft pulp (OKP). Examples of semi-chemical pulps include semi-chemical pulp (SCP) and chemi-ground wood pulp (CGP), groundwood pulp (GP), and mechanical pulp such as thermomechanical pulp (TMP, BCTMP), but are not particularly limited thereto. Examples of non-wood pulp include, but are not limited to, cotton-based pulp such as cotton linters and cotton lint, non-wood pulp such as hemp, straw, and bagasse, and cellulose, chitin, and chitosan isolated from sea squirts and seaweed. Examples of deinked pulp include, but are not limited to, deinked pulp made from waste paper. The pulp of this embodiment may be used alone or in combination of two or more. Among the above pulps, wood pulp and deinked pulp containing cellulose are preferred in terms of ease of availability. Among wood pulps, chemical pulp has a high cellulose ratio, so that the yield of fine fibrous cellulose during fiber finening (fibrillation) is high, and the decomposition of cellulose in the pulp is small, and fine fibrous cellulose with long fibers having a large axial ratio can be obtained. Among them, kraft pulp and sulfite pulp are most preferably selected. Sheets containing fine fibrous cellulose with long fibers having a large axial ratio tend to have high strength.

[0027] The average fiber width of the fine fibrous cellulose is 1000 nm or less when observed under an electron microscope. The average fiber width is preferably 2 nm or more and 1000 nm or less, more preferably 2 nm or more and 100 nm or less, more preferably 2 nm or more and 50 nm or less, and even more preferably 2 nm or more and 10 nm or less, but is not particularly limited. If the average fiber width of the fine fibrous cellulose is less than 2 nm, it is dissolved in water as cellulose molecules, and therefore tends to be difficult to exhibit the physical properties (strength, rigidity, dimensional stability) of the fine fibrous cellulose. Note that the fine fibrous cellulose is, for example, a single-fiber cellulose having a fiber width of 1000 nm or less.

[0028] Measurement of fiber width of fine fibrous cellulose by electron microscope observation is carried out as follows. An aqueous suspension of fine fibrous cellulose with a concentration of 0.05% by mass to 0.1% by mass is prepared, and this suspension is cast on a hydrophilically treated carbon film-coated grid to prepare a sample for TEM observation. When wide fibers are included, an SEM image of the surface cast on glass may be observed. Observation is carried out using an electron microscope image at a magnification of 1000x, 5000x, 10000x, or 50000x depending on the width of the constituent fibers. However, the sample, observation conditions, and magnification are adjusted to satisfy the following conditions.

[0029] (1) A straight line X is drawn at any point within the observed image, and 20 or more fibers intersect with the straight line X. (2) Within the same image, draw a line Y that intersects the line perpendicularly, and have 20 or more fibers intersect with the line Y.

[0030] For the observed images that satisfy the above conditions, the width of the fibers that intersect with the lines X and Y is visually read. In this way, three or more sets of images of at least non-overlapping surface portions are observed, and the width of the fibers that intersect with the lines X and Y is read for each image. In this way, the fiber widths of at least 20 x 2 x 3 = 120 fibers are read. The average fiber width of the fine fibrous cellulose (sometimes simply called "fiber width") is the average value of the fiber widths read in this way.

[0031] The fiber length of the fine fibrous cellulose is not particularly limited, but is preferably 0.1 μm to 1000 μm, more preferably 0.1 μm to 800 μm, and particularly preferably 0.1 μm to 600 μm. By setting the fiber length within the above range, the destruction of the crystalline region of the fine fibrous cellulose can be suppressed, and the slurry viscosity of the fine fibrous cellulose can be set to an appropriate range. The fiber length of the fine fibrous cellulose can be determined by image analysis using TEM, SEM, and AFM.

[0032] The fine fibrous cellulose preferably has a type I crystal structure. The fact that the fine fibrous cellulose has a type I crystal structure can be identified from a diffraction profile obtained from a wide-angle X-ray diffraction photograph using CuKα (λ=1.5418 Å) monochromated with graphite. Specifically, it can be identified from the presence of typical peaks at two positions, around 2θ=14° to 17° and around 2θ=22° to 23°. The proportion of I-type crystal structure in the fine fibrous cellulose is preferably 30% or more, more preferably 50% or more, and even more preferably 70% or more. In this case, even more excellent performance can be expected in terms of heat resistance and low linear thermal expansion coefficient. The degree of crystallinity can be determined by measuring an X-ray diffraction profile and using the pattern in a conventional manner (Seagal et al., Textile Research Journal, Vol. 29, p. 786, 1959).

[0033] The fine fibrous cellulose preferably has a phosphate group or a substituent derived from a phosphate group. The phosphate group is a divalent functional group obtained by removing a hydroxyl group from phosphoric acid. Specifically, -PO 3 H 2 The substituent derived from the phosphate group includes a group formed by condensation polymerization of a phosphate group, a salt of a phosphate group, a phosphate ester group, and the like, and may be either an ionic or nonionic substituent.

[0034] In the present invention, the phosphate group or a substituent derived from a phosphate group may be a substituent represented by the following formula (1). [ka]

[0035] In formula (1), a, b, m, and n each independently represent an integer (wherein a=b×m); n (n=an integer from 1 to n) and α' each independently represent R or OR. R is a hydrogen atom, a saturated linear hydrocarbon group, a saturated branched hydrocarbon group, a saturated cyclic hydrocarbon group, an unsaturated linear hydrocarbon group, an unsaturated branched hydrocarbon group, an aromatic group, or a group derived therefrom; β is an organic or inorganic cation having a valence of one or more.

[0036] <Phosphate group introduction step> The phosphate group introduction step can be carried out by reacting at least one compound having a phosphate group and its salt (hereinafter referred to as "phosphorylation reagent" or "compound A") with a fiber raw material containing cellulose. Such a phosphorylation reagent may be mixed in the form of a powder or an aqueous solution with the fiber raw material in a dry or wet state. As another example, a powder or an aqueous solution of the phosphorylation reagent may be added to a slurry of the fiber raw material.

[0037] The phosphate group introduction step can be carried out by reacting at least one compound having a phosphate group and its salt (phosphorylation reagent or compound A) with a fiber raw material containing cellulose. This reaction may be carried out in the presence of at least one compound selected from urea and its derivatives (hereinafter referred to as "compound B").

[0038] One example of a method for acting compound A on a fiber raw material in the presence of compound B is a method of mixing powders or an aqueous solution of compound A and compound B with a dry or wet fiber raw material. Another example is a method of adding powders or an aqueous solution of compound A and compound B to a slurry of the fiber raw material. Of these, the method of adding an aqueous solution of compound A and compound B to a dry fiber raw material, or the method of adding powders or an aqueous solution of compound A and compound B to a wet fiber raw material is preferred because of high uniformity of the reaction. Compound A and compound B may be added simultaneously or separately. Compound A and compound B to be reacted may be added as an aqueous solution first, and excess chemical solution may be removed by squeezing. The form of the fiber raw material is preferably cotton-like or thin sheet-like, but is not particularly limited.

[0039] Compound A used in this embodiment is at least one selected from compounds having a phosphate group and salts thereof. Examples of compounds having a phosphate group include, but are not limited to, phosphoric acid, lithium salts of phosphoric acid, sodium salts of phosphoric acid, potassium salts of phosphoric acid, and ammonium salts of phosphoric acid. Examples of lithium salts of phosphoric acid include lithium dihydrogen phosphate, dilithium hydrogen phosphate, trilithium phosphate, lithium pyrophosphate, and lithium polyphosphate. Examples of sodium salts of phosphoric acid include sodium dihydrogen phosphate, disodium hydrogen phosphate, trisodium phosphate, sodium pyrophosphate, and sodium polyphosphate. Examples of potassium salts of phosphoric acid include potassium dihydrogen phosphate, dipotassium hydrogen phosphate, tripotassium phosphate, potassium pyrophosphate, and potassium polyphosphate. Examples of ammonium salts of phosphoric acid include ammonium dihydrogen phosphate, diammonium hydrogen phosphate, triammonium phosphate, ammonium pyrophosphate, and ammonium polyphosphate.

[0040] Among these, phosphoric acid, sodium salts of phosphoric acid, potassium salts of phosphoric acid, and ammonium salts of phosphoric acid are preferred from the viewpoints of high efficiency of introduction of phosphate groups, easier improvement of defibration efficiency in the defibration step described below, low cost, and ease of industrial application, and sodium dihydrogen phosphate or disodium hydrogen phosphate is more preferred.

[0041] In addition, it is preferable to use compound A as an aqueous solution, since the uniformity of the reaction is improved and the efficiency of introducing the phosphate group is increased. The pH of the aqueous solution of compound A is not particularly limited, but it is preferably 7 or less, since the efficiency of introducing the phosphate group is increased, and from the viewpoint of suppressing hydrolysis of pulp fibers, it is more preferable to have a pH of 3 or more and a pH of 7 or less. The pH of the aqueous solution of compound A may be adjusted, for example, by using an acidic compound and an alkaline compound among compounds having a phosphate group in combination and changing the quantitative ratio. The pH of the aqueous solution of compound A may be adjusted by adding an inorganic alkali or an organic alkali to the acidic compound among compounds having a phosphate group.

[0042] The amount of compound A added to the fiber raw material is not particularly limited, but when the amount of compound A added is converted into the amount of phosphorus atoms, the amount of phosphorus atoms added to the fiber raw material (bone dry mass) is preferably 0.5% by mass or more and 100% by mass or less, more preferably 1% by mass or more and 50% by mass or less, and most preferably 2% by mass or more and 30% by mass or less. If the amount of phosphorus atoms added to the fiber raw material is within the above range, the yield of fine fibrous cellulose can be further improved. In addition, by setting the amount of phosphorus atoms added to the fiber raw material to 100% by mass or less, the cost of compound A used can be reduced while increasing the phosphorylation efficiency.

[0043] Compound B used in this embodiment includes urea, biuret, 1-phenylurea, 1-benzylurea, 1-methylurea, 1-ethylurea, and the like.

[0044] Like compound A, compound B is preferably used as an aqueous solution. In addition, it is preferable to use an aqueous solution in which both compound A and compound B are dissolved, as this increases the uniformity of the reaction. The amount of compound B added to the fiber raw material (bone dry mass) is preferably 1% by mass or more and 500% by mass or less, more preferably 10% by mass or more and 400% by mass or less, even more preferably 100% by mass or more and 350% by mass or less, and particularly preferably 150% by mass or more and 300% by mass or less.

[0045] In addition to compound A and compound B, amides or amines may be included in the reaction system. Examples of amides include formamide, dimethylformamide, acetamide, and dimethylacetamide. Examples of amines include methylamine, ethylamine, trimethylamine, triethylamine, monoethanolamine, diethanolamine, triethanolamine, pyridine, ethylenediamine, and hexamethylenediamine. Among these, triethylamine in particular is known to act as a good reaction catalyst.

[0046] In the phosphoric acid group introduction step, a heat treatment is preferably performed. The heat treatment temperature is preferably selected so that the phosphoric acid group can be efficiently introduced while suppressing thermal decomposition and hydrolysis of the fiber. Specifically, the heat treatment temperature is preferably 50°C or higher and 300°C or lower, more preferably 100°C or higher and 250°C or lower, and even more preferably 130°C or higher and 200°C or lower. For heating, a reduced pressure dryer, an infrared heating device, or a microwave heating device may be used.

[0047] During the heat treatment, if the fiber raw material is left standing for a long time while the fiber raw material slurry containing compound A contains water, the water molecules and the dissolved compound A move to the surface of the fiber raw material as it dries. Therefore, the concentration of compound A in the fiber raw material may become uneven, and the introduction of phosphate groups to the fiber surface may not proceed uniformly. In order to prevent the occurrence of uneven concentration of compound A in the fiber raw material due to drying, a very thin sheet-like fiber raw material may be used, or a method may be adopted in which the fiber raw material and compound A are kneaded or stirred in a kneader or the like while being heated and dried or dried under reduced pressure.

[0048] The heating device used in the heat treatment is preferably a device that can constantly discharge moisture held by the slurry and moisture generated by the addition reaction of phosphate groups and the like to hydroxyl groups of the fibers outside the device system, and is, for example, a fan-type oven, etc. If moisture within the device system is constantly discharged, not only can the hydrolysis reaction of phosphate ester bonds, which is the reverse reaction of phosphate esterification, be suppressed, but also acid hydrolysis of sugar chains in the fibers can be suppressed, and fine fibers with a high axial ratio can be obtained.

[0049] The heat treatment time is affected by the heating temperature, but is preferably from 1 second to 300 minutes after the water is substantially removed from the fiber raw material slurry, more preferably from 1 second to 1000 seconds, and even more preferably from 10 seconds to 800 seconds. In the present invention, the amount of phosphate groups introduced can be kept within a preferred range by setting the heating temperature and heating time within appropriate ranges.

[0050] The amount of phosphate group introduced is preferably 0.1 mmol / g to 3.65 mmol / g per 1 g (mass) of fine fibrous cellulose, more preferably 0.14 mmol / g to 3.5 mmol / g, even more preferably 0.2 mmol / g to 3.2 mmol / g, particularly preferably 0.4 mmol / g to 3.0 mmol / g, and most preferably 0.6 mmol / g to 2.5 mmol / g. By setting the amount of phosphate group introduced within the above range, it is possible to easily pulverize the fiber raw material and increase the stability of the fine fibrous cellulose. In addition, by setting the amount of phosphate group introduced within the above range, it is possible to easily pulverize the fiber raw material while leaving hydrogen bonds between the fine fibrous cellulose, and good strength can be expected in the sheet.

[0051] The amount of phosphate groups introduced into the fiber raw material can be measured by a conductometric titration method. Specifically, the fiber is pulverized by a defibration process, the resulting fine fibrous cellulose-containing slurry is treated with an ion exchange resin, and then an aqueous sodium hydroxide solution is added to measure the change in electrical conductivity, thereby measuring the amount introduced.

[0052] In the conductometric titration, the curve shown in Figure 1 is obtained when an alkali is added. At first, the electrical conductivity drops sharply (hereinafter referred to as the "first region"). After that, the conductivity starts to increase slightly (hereinafter referred to as the "second region"). After that, the increment of the conductivity increases (hereinafter referred to as the "third region"). That is, three regions appear. Of these, the amount of alkali required in the first region is equal to the amount of strong acid groups in the slurry used for titration, and the amount of alkali required in the second region is equal to the amount of weak acid groups in the slurry used for titration. When phosphate groups undergo condensation, the weak acid groups are apparently lost, and the amount of alkali required in the second region is less than the amount of alkali required in the first region. On the other hand, the amount of strong acid groups corresponds to the amount of phosphorus atoms regardless of the presence or absence of condensation, so when simply referring to the amount of phosphate groups introduced (or the amount of phosphate groups) or the amount of substituents introduced (or the amount of substituents), it refers to the amount of strong acid groups. That is, the amount of alkali (mmol) required in the first region of the curve shown in FIG. 1 is divided by the solid content (g) in the slurry to be titrated to obtain the amount of introduced substituent (mmol / g).

[0053] The phosphate group introduction step may be carried out at least once, but may also be repeated multiple times, which is preferable since more phosphate groups can be introduced in this case.

[0054] <Introduction of carboxyl group> In the present invention, when the fine fibrous cellulose has a carboxyl group, the carboxyl group can be introduced, for example, by subjecting the fiber raw material to an oxidation treatment such as TEMPO oxidation treatment, or by treating the raw material with a compound having a group derived from carboxylic acid, a derivative thereof, or an acid anhydride or a derivative thereof.

[0055] The compound having a carboxyl group is not particularly limited, but examples thereof include dicarboxylic acid compounds such as maleic acid, succinic acid, phthalic acid, fumaric acid, glutaric acid, adipic acid, and itaconic acid, and tricarboxylic acid compounds such as citric acid and aconitic acid.

[0056] The acid anhydride of a compound having a carboxyl group is not particularly limited, but examples thereof include acid anhydrides of dicarboxylic acid compounds such as maleic anhydride, succinic anhydride, phthalic anhydride, glutaric anhydride, adipic anhydride, and itaconic anhydride.

[0057] The derivative of a compound having a carboxyl group is not particularly limited, but includes imidized products of acid anhydrides of compounds having a carboxyl group, and derivatives of acid anhydrides of compounds having a carboxyl group. The imidized products of acid anhydrides of compounds having a carboxyl group are not particularly limited, but include imidized products of dicarboxylic acid compounds such as maleimide, succinimide, and phthalimide.

[0058] The derivative of the acid anhydride of the compound having a carboxyl group is not particularly limited, and examples thereof include those in which at least a part of the hydrogen atoms of the acid anhydride of the compound having a carboxyl group is substituted with a substituent (e.g., an alkyl group, a phenyl group, etc.), such as dimethylmaleic anhydride, diethylmaleic anhydride, and diphenylmaleic anhydride.

[0059] <Alkaline treatment> When producing fine fibrous cellulose, an alkali treatment may be carried out between the ionic functional group introduction step and the defibration step described below. The alkali treatment method is not particularly limited, but may be, for example, a method of immersing the functional group-introduced fiber in an alkali solution. The alkaline compound contained in the alkaline solution is not particularly limited, but may be an inorganic alkaline compound or an organic alkaline compound. The solvent in the alkaline solution may be either water or an organic solvent. The solvent is preferably a polar solvent (water or a polar organic solvent such as alcohol), and more preferably an aqueous solvent containing at least water. Among the alkaline solutions, an aqueous solution of sodium hydroxide or an aqueous solution of potassium hydroxide is particularly preferred because of its high versatility.

[0060] The temperature of the alkaline solution in the alkaline treatment step is not particularly limited, but is preferably from 5°C to 80°C, and more preferably from 10°C to 60°C. The immersion time in the alkaline solution in the alkaline treatment step is not particularly limited, but is preferably from 5 to 30 minutes, and more preferably from 10 to 20 minutes. The amount of the alkaline solution used in the alkaline treatment is not particularly limited, but is preferably from 100% to 100,000% by mass, more preferably from 1,000% to 10,000% by mass, based on the absolute dry mass of the phosphate group-introduced fiber.

[0061] In order to reduce the amount of alkaline solution used in the alkaline treatment step, the functionalized fiber may be washed with water or an organic solvent before the alkaline treatment step. After the alkaline treatment, in order to improve the handleability, it is preferable to wash the alkaline-treated functionalized fiber with water or an organic solvent before the defibration treatment step.

[0062] <Defibrillation processing> The ionic functional group-introduced fibers are defibrated in a defibration treatment step. In the defibration treatment step, the fibers are usually defibrated using a defibration treatment device to obtain a slurry containing fine fibrous cellulose, but the treatment device and treatment method are not particularly limited. As the defibration treatment device, a high-speed defibrator, a grinder (stone mill type grinder), a high-pressure homogenizer, an ultra-high-pressure homogenizer, a high-pressure collision type grinder, a ball mill, a bead mill, etc. can be used. Alternatively, as the defibration treatment device, a wet grinding device such as a disk type refiner, a conical refiner, a biaxial kneader, a vibration mill, a homomixer under high-speed rotation, an ultrasonic disperser, or a beater can be used. The defibration treatment device is not limited to the above. Preferred defibration treatment methods include a high-speed defibrator, a high-pressure homogenizer, and an ultra-high-pressure homogenizer, which are less affected by the grinding media and have little risk of contamination.

[0063] In the defibration process, it is preferable to dilute the fiber raw material with water and an organic solvent, either alone or in combination, to form a slurry, but there is no particular limitation. As the dispersion medium, a polar organic solvent can be used in addition to water. Preferred polar organic solvents include, but are not limited to, alcohols, ketones, ethers, dimethyl sulfoxide (DMSO), dimethylformamide (DMF), or dimethylacetamide (DMAc). Examples of alcohols include methanol, ethanol, n-propanol, isopropanol, n-butanol, or t-butyl alcohol. Examples of ketones include acetone or methyl ethyl ketone (MEK). Examples of ethers include diethyl ether or tetrahydrofuran (THF). The dispersion medium may be one type or two or more types. In addition, the dispersion medium may contain solids other than the fiber raw material, such as urea having hydrogen bonding properties.

[0064] The fine fibrous cellulose may be obtained by concentrating and / or drying the fine fibrous cellulose-containing slurry obtained by the defibration treatment once, and then subjecting the slurry to defibration treatment again. In this case, the method of concentration and drying is not particularly limited, and examples thereof include a method of adding a thickening agent to a slurry containing fine fibrous cellulose, and a method of using a commonly used dehydrator, press, or dryer. In addition, known methods such as those described in WO2014 / 024876, WO2012 / 107642, and WO2013 / 121086 can be used. In addition, the fine fibrous cellulose-containing slurry can be concentrated and dried by forming it into a sheet, and the sheet can be subjected to defibration treatment to obtain a fine fibrous cellulose-containing slurry again.

[0065] The equipment used to defibrate (grind) the fine fibrous cellulose slurry again after concentrating and / or drying includes, but is not limited to, wet grinding equipment such as a high-speed defibrator, grinder (stone mill type grinder), high-pressure homogenizer, ultra-high-pressure homogenizer, high-pressure collision type grinder, ball mill, bead mill, disk type refiner, conical refiner, biaxial kneader, vibration mill, homomixer under high-speed rotation, ultrasonic disperser, beater, etc.

[0066] (Polymer) The sheet of the present invention contains a polymer containing units derived from a polyol and units derived from a nitrogen-containing compound.

[0067] The polyol, which is a compound from which the polyol-derived unit is derived, is a compound having two or more hydroxyl groups in one molecule. The polyol is preferably a compound having 2 to 6 hydroxyl groups, more preferably a compound having 2 to 4 hydroxyl groups, even more preferably a compound having 2 or 3 hydroxyl groups, and particularly preferably a compound having 2 hydroxyl groups. In other words, the polyol-derived unit is preferably a unit derived from a diol.

[0068] Examples of the polyol include polyester polyol, polycaprolactone polyol, polyether polyol, polycarbonate polyol, polybutadiene polyol, hydrogenated polybutadiene polyol, polyacrylic polyol, dimer diol, and hydrogenated dimer diol. In addition, examples of low molecular weight polyols include ethylene glycol, diethylene glycol, 1,2-propanediol, 1,3-propanediol, 2-methyl-1,3-propanediol, 2-butyl-2-ethyl-1,3-propanediol, 1,3-butanediol, 1,4-butanediol, neopentyl glycol (2,2-dimethyl-1,3-propanediol), 2-isopropyl-1,4-butanediol, 3-methyl-2,4-pentanediol, 2,4-pentanediol, 1,5-pentanediol, 3-methyl-1,5-pentanediol, 2-methyl-2,4-pentanediol, 2,4-dimethyl-1,5-pentanediol, 2,4-diethyl-1,5-pentanediol, 1,5-hexanediol, 1,6-hexanediol, 2-ethyl-1,3- Examples of the polyol-derived unit include aliphatic diols such as hexanediol, 2-ethyl-1,6-hexanediol, 1,7-heptanediol, 3,5-heptanediol, 1,8-octanediol, 2-methyl-1,8-octanediol, 1,9-nonanediol, and 1,10-decanediol; alicyclic diols such as cyclohexanedimethanol (e.g., 1,4-cyclohexanedimethanol), cyclohexanediol (e.g., 1,3-cyclohexanediol, 1,4-cyclohexanediol), and 2-bis(4-hydroxycyclohexyl)-propane; and polyols having three or more valences such as trimethylolethane, trimethylolpropane, hexitols, pentitols, glycerin, polyglycerin, pentaerythritol, dipentaerythritol, and tetramethylolpropane. Among these, the polyol-derived unit is preferably a unit derived from at least one selected from ethylene glycol, diethylene glycol, and polyether polyol.

[0069] The nitrogen-containing compound, which is the compound derived from the nitrogen-containing compound-derived unit, may be any compound containing a nitrogen atom, and is preferably a compound having a carbon-nitrogen bond. In addition, such a nitrogen-containing compound is preferably a compound having a group that reacts with the hydroxyl group of the polyol, which is the compound derived from the polyol-derived unit, and more preferably a compound having two or more groups that react with the hydroxyl group of the polyol. Examples of such nitrogen-containing compounds include isocyanate compounds, carbodiimide compounds, oxazoline compounds, aziridine compounds, and melamine compounds. Among them, the nitrogen-containing compound is preferably at least one selected from isocyanate compounds and carbodiimide compounds, and more preferably at least one selected from diisocyanate compounds and dicarbodiimide compounds. That is, the unit derived from the nitrogen-containing compound is preferably a unit derived from at least one selected from isocyanate compounds and carbodiimide compounds, and more preferably a unit derived from at least one selected from diisocyanate compounds and dicarbodiimide compounds. The isocyanate compound is a compound having an isocyanate group, and the carbodiimide compound is a compound having a carbodiimide group.

[0070] When the unit derived from the nitrogen-containing compound is a unit derived from an isocyanate compound, the polymer containing the unit derived from the polyol and the unit derived from the nitrogen-containing compound is preferably a urethane polymer. For example, when the unit derived from the polyol is a unit derived from a diol and the unit derived from the nitrogen-containing compound is a unit derived from a diisocyanate compound, the urethane polymer is preferably a polymer having the following structure:

[0071] [ka]

[0072] In the above structural formula, R 1 and R 2 each independently represents a divalent organic group, and n represents an integer of 2 or more. 1is preferably the residue of a diol, R 2 is preferably a residue of a diisocyanate compound. Here, the residue of a diol refers to a group constituting a portion obtained by removing a hydroxyl group from a diol, and the residue of a diisocyanate compound refers to a group constituting a portion obtained by removing an isocyanate group from a diisocyanate compound. In the above structural formula, the portion surrounded by the dotted line is a unit derived from a polyol, and the other portions are units derived from a nitrogen-containing compound.

[0073] As the urethane polymer, a commercially available urethane prepolymer may be used. For example, a urethane prepolymer water dispersion (Elastron H-3-NS, solid content concentration 23.1% by mass) manufactured by Daiichi Kogyo Seiyaku Co., Ltd. may be used. In addition, a urethane polymer polymerized using the above-mentioned polyol and isocyanate compound may be used.

[0074] Alternatively, a polymer may be prepared by using a polyether polyol as the polyol and a polycarbodiimide compound as the nitrogen-containing compound. As the polyether polyol, for example, polyethylene glycol having a number average molecular weight of 100 to 1000 can be used. As the above polymer, for example, a polymer having the following structure is preferable.

[0075] [ka]

[0076] In the above structural formula, R 1 ~R 5 each independently represents a divalent organic group, and n represents an integer of 2 or more. 1 and R 2 are each independently preferably a residue of a polyether polyol, 3 ~R 5 is preferably each independently a residue of a polycarbodiimide compound. In the above structural formula, the portion enclosed by the dotted line is a unit derived from a polyol, and the other portions are units derived from a nitrogen-containing compound.

[0077] The content of the polymer containing the unit derived from the polyol and the unit derived from the nitrogen-containing compound is preferably 10% by mass or more, more preferably 20% by mass or more, and even more preferably 35% by mass or more, based on the total mass of the sheet. The content of the fine fibrous cellulose is preferably 90% by mass or less, more preferably 80% by mass or less. By setting the content of the polymer containing the unit derived from the polyol and the unit derived from the nitrogen-containing compound within the above range, the tensile strength of the sheet can be more effectively increased.

[0078] (Reaction catalyst) In the manufacturing process of the sheet of the present invention, a reaction catalyst may be further added to promote polymerization of the polymer. For example, when the unit derived from the nitrogen-containing compound is a unit derived from a diisocyanate compound, it is preferable to use a reaction catalyst to promote the polymerization reaction and / or crosslinking reaction between the isocyanate compound and the polyol. This makes it possible to shorten the heat treatment time during polymerization, etc.

[0079] Examples of the reaction catalyst include organotin compounds, organozinc compounds, organozirconium compounds, organocadmium compounds, organobalium compounds, and amine compounds. Of these, organotin compounds are preferably used as the reaction catalyst. The reaction catalyst is used in the synthesis of a polymer, but at least a part of the reaction catalyst may be ultimately contained in the sheet.

[0080] (optional ingredient) The sheet of the present invention may contain optional components other than the above-mentioned components. Examples of the optional components include antifoaming agents, lubricants, ultraviolet absorbers, dyes, pigments, stabilizers, surfactants, etc. Examples of the optional components include hydrophilic polymers (excluding cellulose fibers) and organic ions, etc.

[0081] (Sheet manufacturing method) The sheet manufacturing process includes a step of obtaining a slurry containing fibrous cellulose having a fiber width of 1000 nm or less and a polymer containing a unit derived from a polyol and a unit derived from a nitrogen-containing compound, and a step of coating the slurry on a substrate or a step of making paper from the slurry. Among them, the sheet manufacturing process preferably includes a step of coating a substrate with a slurry (hereinafter sometimes simply referred to as a slurry) containing fine fibrous cellulose and a polymer containing a unit derived from a polyol and a unit derived from a nitrogen-containing compound. In addition, the fine fibrous cellulose is preferably phosphorylated fine fibrous cellulose.

[0082] In the step of obtaining a slurry, the polymer containing the polyol-derived unit and the nitrogen-containing compound-derived unit is added in an amount of preferably 10% by mass or more, more preferably 20% by mass or more, and even more preferably 35% by mass or more, based on the total mass of the fine fibrous cellulose and the polymer containing the polyol-derived unit and the nitrogen-containing compound-derived unit. Also, the polymer containing the polyol-derived unit and the nitrogen-containing compound-derived unit is added in an amount of preferably 90% by mass or less, more preferably 80% by mass or less.

[0083] In the step of obtaining the slurry, a polymer containing units derived from a polyol and units derived from a nitrogen-containing compound may be added in the state of a prepolymer, or the units derived from a polyol and the units derived from a nitrogen-containing compound may be added separately to form a polymer in the slurry.

[0084] In addition, in the step of obtaining the slurry, a reaction catalyst may be added as necessary. Examples of the reaction catalyst include the reaction catalysts described above. When a reaction catalyst is added in the step of obtaining the slurry, the amount of the reaction catalyst added is preferably 0.5 parts by mass or more and 10 parts by mass or less, and more preferably 1 part by mass or more and 5 parts by mass or less, relative to 100 parts by mass of the polymer. When the unit derived from the nitrogen-containing compound is a unit derived from a diisocyanate compound, the amount of the reaction catalyst added is preferably 0.5 parts by mass or more and 10 parts by mass or less, and more preferably 1 part by mass or more and 5 parts by mass or less, relative to 100 parts by mass of the solid content of the urethane prepolymer.

[0085] <Coating process> The coating process is a process in which a slurry containing fine fibrous cellulose and a polymer containing a unit derived from a polyol and a unit derived from a nitrogen-containing compound is coated on a substrate, and the resulting sheet is dried and peeled off from the substrate to obtain a sheet. By using a coating device and a long substrate, the sheet can be produced continuously.

[0086] The quality of the substrate used in the coating process is not particularly limited, but a substrate with high wettability to the slurry is better in that it can suppress the shrinkage of the sheet during drying, but it is preferable to select a substrate from which the sheet formed after drying can be easily peeled off. Among them, a resin plate or a metal plate is preferable, but is not particularly limited. For example, resin plates such as acrylic plates, polyethylene terephthalate plates, polyvinyl chloride plates, polystyrene plates, and polyvinylidene chloride plates, metal plates such as aluminum plates, zinc plates, copper plates, and iron plates, and those whose surfaces have been oxidized, stainless steel plates, brass plates, etc. can be used.

[0087] In the coating process, if the viscosity of the slurry is low and it spreads on the substrate, a damming frame may be fixed on the substrate to obtain a sheet of a predetermined thickness and basis weight. The quality of the damming frame is not particularly limited, but it is preferable to select one that allows the end of the sheet to be easily peeled off after drying. Among them, a molded resin plate or metal plate is preferable, but is not particularly limited. For example, resin plates such as acrylic plates, polyethylene terephthalate plates, vinyl chloride plates, polystyrene plates, and polyvinylidene chloride plates, metal plates such as aluminum plates, zinc plates, copper plates, and iron plates, and those whose surfaces have been oxidized, stainless steel plates, brass plates, and the like can be used.

[0088] Examples of the coater that can be used to coat the slurry include a roll coater, a gravure coater, a die coater, a curtain coater, an air doctor coater, etc. The die coater, the curtain coater, and the spray coater are preferred because they can achieve a more uniform thickness.

[0089] The coating temperature is not particularly limited, but is preferably from 20° C. to 45° C., more preferably from 25° C. to 40° C., and even more preferably from 27° C. to 35° C. If the coating temperature is equal to or higher than the lower limit, the slurry can be easily coated, and if the coating temperature is equal to or lower than the upper limit, evaporation of the dispersion medium during coating can be suppressed.

[0090] In the coating process, the finished sheet weight is 10 g / m 2 More than 100g / m 2 Less than 20 g / m 2 More than 60g / m 2 It is preferable to coat the slurry so that the basis weight falls within the above range. By coating the slurry so that the basis weight falls within the above range, a sheet with excellent strength can be obtained.

[0091] The coating step preferably includes a step of drying the slurry coated on the substrate. The drying method is not particularly limited, but may be either a non-contact drying method or a method of drying while restraining the sheet, or a combination of these methods.

[0092] As the non-contact drying method, there is no particular limitation, but a method of drying by heating with hot air, infrared rays, far infrared rays or near infrared rays (heat drying method), and a method of drying by vacuum (vacuum drying method) can be applied. The heat drying method and the vacuum drying method may be combined, but the heat drying method is usually applied. Drying by infrared rays, far infrared rays or near infrared rays can be performed using an infrared device, a far infrared device or a near infrared device, but is not particularly limited. The heating temperature in the heat drying method is not particularly limited, but is preferably 20°C or higher and 150°C or lower, and more preferably 25°C or higher and 105°C or lower. If the heating temperature is set to the above lower limit value or higher, the dispersion medium can be quickly volatilized, and if the heating temperature is set to the above upper limit value or lower, the cost required for heating can be suppressed and the discoloration of the fine fibrous cellulose due to heat can be suppressed.

[0093] <Paper making process> The sheet manufacturing process may include a process of making a slurry containing fine fibrous cellulose and a polymer containing a unit derived from a polyol and a unit derived from a nitrogen-containing compound. Examples of the papermaking machine in the papermaking process include a fourdrinier type, a cylinder type, a tilt type, or other continuous papermaking machine, and a multi-layer papermaking machine that combines these. In the papermaking process, known papermaking such as handmaking may be performed.

[0094] In the papermaking process, the slurry is filtered and dehydrated on a wire to obtain a sheet in a wet paper state, and then pressed and dried to obtain a sheet. When filtering and dehydrating the slurry, the filter cloth used during filtration is not particularly limited, but it is important that polymers containing fine fibrous cellulose, units derived from polyols, and units derived from nitrogen-containing compounds do not pass through and that the filtration rate does not become too slow. Although such filter cloth is not particularly limited, a sheet, fabric, or porous membrane made of an organic polymer is preferable. Although the organic polymer is not particularly limited, a non-cellulose organic polymer such as polyethylene terephthalate, polyethylene, polypropylene, polytetrafluoroethylene (PTFE), etc. is preferable. Specifically, a porous membrane of polytetrafluoroethylene having a pore size of 0.1 μm or more and 20 μm or less, for example, 1 μm, a pore size of polyethylene terephthalate or polyethylene fabric having a pore size of 0.1 μm or more and 20 μm or less, for example, 1 μm, etc. are included, but are not particularly limited.

[0095] The method for producing a sheet from the slurry is not particularly limited, but examples thereof include a method using a production apparatus described in WO2011 / 013567. This production apparatus includes a water squeezing section in which a slurry containing fine fibrous cellulose is discharged onto an upper surface of an endless belt and the dispersion medium is squeezed out of the discharged slurry to produce a web, and a drying section in which the web is dried to produce a fiber sheet. An endless belt is disposed between the water squeezing section and the drying section, and the web produced in the water squeezing section is transported to the drying section while still placed on the endless belt.

[0096] The dehydration method that can be used is not particularly limited, but includes dehydration methods that are commonly used in paper production, and is preferably a method of dehydrating with a roll press after dehydrating with a fourdrinier, cylinder, inclined wire, etc. Furthermore, the drying method is not particularly limited, but includes a method that is used in paper production, and is preferably a method such as a cylinder dryer, Yankee dryer, hot air drying, near-infrared heater, or infrared heater.

[0097] (Heating process) The sheet production process preferably further includes a heating step after the step of coating the slurry on a substrate or the step of making paper from the slurry, in which the sheet obtained in the step of coating the slurry on a substrate or the step of making paper from the slurry is heated to further promote polymerization and / or crosslinking of the nitrogen-containing compound and the polyol.

[0098] In the heating step, the sheet obtained in the step of coating the slurry on the substrate or the step of making paper from the slurry is preferably heated for 1 minute to 100 minutes at a temperature of 20° C. to 150° C. The heating method may be a contact or non-contact heating method, and specifically, a drying method using a cylinder dryer, a Yankee dryer, a hot air dryer, a near-infrared heater, an infrared heater, or the like may be used.

[0099] (Laminate) The present invention may also relate to a laminate having a structure in which another layer is laminated on the sheet. Such another layer may be provided on both surfaces of the sheet, or may be provided only on one surface of the sheet. Examples of the other layer laminated on at least one surface of the sheet include a resin layer and an inorganic layer.

[0100] Specific examples of the laminate include a laminate in which a resin layer is directly laminated on at least one surface of a sheet, a laminate in which an inorganic layer is directly laminated on at least one surface of a sheet, a laminate in which a resin layer, a sheet, and an inorganic layer are laminated in this order, a laminate in which a sheet, a resin layer, and an inorganic layer are laminated in this order, and a laminate in which a sheet, an inorganic layer, and a resin layer are laminated in this order. The layer structure of the laminate is not limited to the above, and can be in various modes depending on the application.

[0101] <Resin layer> The resin layer is a layer whose main component is a natural resin or a synthetic resin. Here, the main component refers to a component contained in an amount of 50% by mass or more with respect to the total mass of the resin layer. The resin content is preferably 60% by mass or more with respect to the total mass of the resin layer, more preferably 70% by mass or more, further preferably 80% by mass or more, and particularly preferably 90% by mass or more. The resin content may be 100% by mass or may be 95% by mass or less.

[0102] Examples of natural resins include rosin-based resins such as rosin, rosin ester, and hydrogenated rosin ester.

[0103] The synthetic resin is preferably at least one selected from, for example, polycarbonate resin, polyethylene terephthalate resin, polyethylene naphthalate resin, polyethylene resin, polypropylene resin, polyimide resin, polystyrene resin, and acrylic resin. Among them, the synthetic resin is preferably at least one selected from polycarbonate resin and acrylic resin, and more preferably polycarbonate resin. The acrylic resin is preferably at least one selected from polyacrylonitrile and poly(meth)acrylate.

[0104] Examples of the polycarbonate resin constituting the resin layer include aromatic polycarbonate resins and aliphatic polycarbonate resins. Specific examples of these polycarbonate resins are known, and examples of such polycarbonate resins include the polycarbonate resins described in JP 2010-023275 A.

[0105] The resin constituting the resin layer may be one type of resin alone, a copolymer obtained by copolymerization or graft polymerization of multiple resin components, or a blend material obtained by mixing multiple resin components by a physical process.

[0106] An adhesive layer may be provided between the sheet and the resin layer, or the sheet and the resin layer may be directly attached without providing an adhesive layer. When an adhesive layer is provided between the sheet and the resin layer, an adhesive constituting the adhesive layer may be, for example, an acrylic resin. In addition, examples of adhesives other than acrylic resins include vinyl chloride resins, (meth)acrylic acid ester resins, styrene / acrylic acid ester copolymer resins, vinyl acetate resins, vinyl acetate / (meth)acrylic acid ester copolymer resins, urethane resins, silicone resins, epoxy resins, ethylene / vinyl acetate copolymer resins, polyester resins, polyvinyl alcohol resins, ethylene-vinyl alcohol copolymer resins, and rubber emulsions such as SBR and NBR.

[0107] When no adhesive layer is provided between the sheet and the resin layer, the resin layer may contain an adhesion aid, and the surface of the resin layer may be subjected to a surface treatment such as hydrophilization. Examples of the adhesion aid include compounds containing at least one selected from an isocyanate group, a carbodiimide group, an epoxy group, an oxazoline group, an amino group, and a silanol group, and organosilicon compounds. Of these, the adhesion aid is preferably at least one selected from a compound containing an isocyanate group (isocyanate compound) and an organosilicon compound. Examples of the organosilicon compound include silane coupling agent condensates and silane coupling agents. Examples of surface treatment methods other than the hydrophilization treatment include corona treatment, plasma discharge treatment, UV irradiation treatment, electron beam irradiation treatment, and flame treatment.

[0108] <Inorganic layer> The material constituting the inorganic layer is not particularly limited, and examples thereof include aluminum, silicon, magnesium, zinc, tin, nickel, titanium; their oxides, carbides, nitrides, oxycarbides, oxynitrides, or oxycarbonitrides; or mixtures thereof. From the viewpoint of stably maintaining high moisture resistance, silicon oxide, silicon nitride, silicon oxide carbide, silicon oxynitride, silicon oxycarbonitride, aluminum oxide, aluminum nitride, aluminum oxide carbide, aluminum oxynitride, or mixtures thereof are preferred.

[0109] The method for forming the inorganic layer is not particularly limited. Generally, the methods for forming a thin film are roughly divided into chemical vapor deposition (CVD) and physical vapor deposition (PVD), and either method may be adopted. Specific examples of the CVD method include plasma CVD using plasma, and catalytic chemical vapor deposition (Cat-CVD) in which a material gas is catalytically decomposed by pyrolysis using a heated catalyst. Specific examples of the PVD method include vacuum deposition, ion plating, sputtering, and the like.

[0110] Atomic layer deposition (ALD) can also be used as a method for forming an inorganic layer. The ALD method is a method for forming a thin film in atomic layer units by alternately supplying the raw material gases of each element that constitutes the film to be formed to the surface on which the layer is to be formed. Although it has the disadvantage of a slow film formation speed, it has the advantage of being able to cover even surfaces with complex shapes neatly and to form a thin film with fewer defects than the plasma CVD method. In addition, the ALD method has the advantage that the film thickness can be controlled to the nano order, and it is relatively easy to cover a large surface. Furthermore, the ALD method is expected to improve the reaction rate, achieve low-temperature processing, and reduce unreacted gas by using plasma.

[0111] (Application) The sheet of the present invention is suitable for use as a light-transmitting substrate for various display devices, various solar cells, etc. It is also suitable for use as a substrate for electronic devices, a component for home appliances, a window material for various vehicles and buildings, an interior material, an exterior material, a packaging material, etc. Furthermore, it is suitable for use as a thread, a filter, a fabric, a cushioning material, a sponge, an abrasive material, etc., and also for use as a reinforcing material for the sheet itself. EXAMPLES

[0112] The features of the present invention will be described in more detail below with reference to examples and comparative examples. The materials, amounts used, ratios, processing contents, processing procedures, etc. shown in the following examples can be appropriately changed without departing from the spirit of the present invention. Therefore, the scope of the present invention should not be interpreted as being limited by the specific examples shown below. In the following, Examples 4 to 8 shall be read as Reference Examples 4 to 8, respectively.

[0113] Example 1 <Preparation of cellulose fibers with phosphoric acid groups> As softwood kraft pulp, Oji Paper pulp (solid content 93% by mass, basis weight 208 g / m 2 A sheet-like pulp (700 ml of Canadian Standard Freeness (CSF) measured according to JIS P 8121 after disintegration) was used. 100 parts by mass (bone dry mass) of the above softwood kraft pulp was impregnated with a mixed aqueous solution of ammonium dihydrogen phosphate and urea, and squeezed to obtain 45 parts by mass of ammonium dihydrogen phosphate and 200 parts by mass of urea, to obtain a chemical-impregnated pulp. The obtained chemical-impregnated pulp was dried and heated for 200 seconds in a hot air dryer at 165°C to introduce phosphate groups into the cellulose in the pulp. The amount of phosphate groups introduced at this time was 0.98 mmol / g.

[0114] The amount of introduced phosphate groups was measured by diluting cellulose with ion-exchange water to a content of 0.2% by mass, treating with ion-exchange resin, and titrating with alkali. In the treatment with ion-exchange resin, 1 / 10 by volume of a strongly acidic ion-exchange resin (Organo Corporation, Amberjet 1024: conditioned) was added to a 0.2% by mass cellulose-containing slurry, and shaking was performed for 1 hour. Then, the slurry was poured onto a mesh with an opening of 90 μm to separate the resin and the slurry. In the titration with alkali, a 0.1 N aqueous sodium hydroxide solution was added to the fibrous cellulose-containing slurry after ion exchange, while measuring the change in the value of the electrical conductivity of the slurry. That is, the amount of alkali (mmol) required in the first region of the curve shown in FIG. 1 was divided by the solid content (g) in the slurry to be titrated to obtain the amount of introduced substituents (mmol / g).

[0115] <Alkaline treatment, cleaning> Next, 5000 ml of ion-exchanged water was added to the cellulose with introduced phosphate groups, and the mixture was stirred and washed, followed by dehydration. The dehydrated pulp was diluted with 5000 ml of ion-exchanged water, and while stirring, 1N aqueous sodium hydroxide solution was gradually added until the pH became 12 to 13, to obtain a pulp dispersion. The pulp dispersion was then dehydrated, and 5000 ml of ion-exchanged water was added for washing. This dehydration and washing was repeated once more.

[0116] <Mechanical processing> Ion-exchanged water was added to the pulp obtained after washing and dehydration to obtain a pulp dispersion with a solid content concentration of 1.0 mass%. This pulp dispersion was treated with a high-pressure homogenizer (Panda Plus 2000, manufactured by NiroSoavi) to obtain a cellulose dispersion. In the treatment using the high-pressure homogenizer, the mixture was passed through a homogenizing chamber five times at an operating pressure of 1200 bar. Furthermore, this cellulose dispersion was treated with a wet-type micronization device (Ultimizer, manufactured by Sugino Machine Co., Ltd.) to obtain a fine fibrous cellulose dispersion (A). In the treatment using the wet-type micronization device, the mixture was passed through a treatment chamber five times at a pressure of 245 MPa. The average fiber width of the fine fibrous cellulose contained in the fine fibrous cellulose dispersion (A) was 4 nm.

[0117] <Mixing polyol and nitrogen-containing compound> The concentration of the fine fibrous cellulose dispersion (A) was adjusted to 0.5% by mass. Then, to 80 parts by mass of the solid content of the fine fibrous cellulose dispersion (A), a urethane prepolymer aqueous dispersion (Dai-ichi Kogyo Seiyaku Co., Ltd., Elastron H-3-NS, solid content concentration 23.1% by mass) consisting of a polyol-derived unit and a nitrogen-containing compound-derived unit (polyisocyanate-derived unit) was added to 20 parts by mass of the urethane prepolymer and stirred. Next, to 20 parts by mass of the urethane prepolymer, a reaction catalyst aqueous dispersion of an isocyanate group (Dai-ichi Kogyo Seiyaku Co., Ltd., Elastron CAT-21, solid content concentration 13.7% by mass) was added to 0.6 parts by mass of the reaction catalyst and stirred to obtain a fine fibrous cellulose dispersion (B).

[0118] <Sheeting> Next, the finished basis weight of the fine fibrous cellulose-containing sheet (sheet composed of the solid content of the fine fibrous cellulose dispersion (B)) was 50 g / m 2The fine fibrous cellulose dispersion (B) was weighed out so that the dispersion was 100% by weight, spread on a commercially available acrylic plate, and dried in a thermohygrostat at 35°C and a relative humidity of 15%. A metal frame for damming (a metal frame with inner dimensions of 180 mm x 180 mm) was placed on the acrylic plate so that the basis weight was the specified. Furthermore, the fine fibrous cellulose-containing sheet formed after drying was peeled off from the acrylic plate and heated at 120°C for 1 hour to promote the reaction between the polyol and the nitrogen-containing compound. A fine fibrous cellulose-containing sheet was obtained by the above procedure. The thickness of the sheet was 25 μm.

[0119] Example 2 In the <Mixing of polyol and nitrogen-containing compound> of Example 1, a urethane prepolymer aqueous dispersion was added to the fine fibrous cellulose dispersion (A) so that the urethane prepolymer was 40 parts by mass per 60 parts by mass of solid content, and stirred. Next, a reaction catalyst aqueous dispersion was added to the fine fibrous cellulose dispersion (A) so that the reaction catalyst was 1.2 parts by mass per 40 parts by mass of the urethane prepolymer, and stirred to obtain a fine fibrous cellulose dispersion (B). The other procedures were the same as in Example 1, and a fine fibrous cellulose-containing sheet was obtained.

[0120] Example 3 In the <Mixing of polyol and nitrogen-containing compound> of Example 1, a urethane prepolymer aqueous dispersion was added to the fine fibrous cellulose dispersion (A) so that the urethane prepolymer was 60 parts by mass per 40 parts by mass of solid content, and stirred. Next, a reaction catalyst aqueous dispersion was added to the fine fibrous cellulose dispersion (A) so that the reaction catalyst was 1.8 parts by mass per 60 parts by mass of the urethane prepolymer, and stirred to obtain a fine fibrous cellulose dispersion (B). The other procedures were the same as in Example 1, and a fine fibrous cellulose-containing sheet was obtained.

[0121] Example 4 In the <Mixing of polyol and nitrogen-containing compound> of Example 1, a urethane prepolymer aqueous dispersion was added to the fine fibrous cellulose dispersion (A) so that the urethane prepolymer was 80 parts by mass per 20 parts by mass of solid content, and the mixture was stirred. Next, a reaction catalyst aqueous dispersion was added to the fine fibrous cellulose dispersion (B) so that the reaction catalyst was 2.4 parts by mass per 80 parts by mass of the urethane prepolymer, and the mixture was stirred. The other procedures were the same as in Example 1, and a fine fibrous cellulose-containing sheet was obtained.

[0122] Example 5 The concentration of the fine fibrous cellulose dispersion (A) obtained in Example 1 was adjusted so that the solid content concentration was 0.5% by mass. Thereafter, 17 parts by mass of polyethylene glycol having a molecular weight of 400 (manufactured by Daiichi Kogyo Seiyaku Co., Ltd., PEG400) was added as a polyol to 67 parts by mass of the solid content of the fine fibrous cellulose dispersion (A) and stirred. Next, an aqueous solution of a polycarbodiimide compound (manufactured by Nisshinbo Chemical Co., Ltd., Carbodilite V-02-L2, solid content concentration 40.1%) was added as a nitrogen-containing compound so that the polycarbodiimide compound was 16 parts by mass to 17 parts by mass of polyethylene glycol, and stirred to obtain a fine fibrous cellulose dispersion (B). The other procedures were the same as in Example 1, and a fine fibrous cellulose-containing sheet was obtained.

[0123] Example 6 In Example 5, 15 parts by mass of polyethylene glycol was added to 57 parts by mass of the solid content of the fine fibrous cellulose dispersion (A) and stirred. Then, an aqueous solution of a polycarbodiimide compound was added to 15 parts by mass of polyethylene glycol so that the polycarbodiimide compound was 28 parts by mass. The other procedures were the same as in Example 5, and a fine fibrous cellulose-containing sheet was obtained.

[0124] Example 7 In Example 5, 11 parts by mass of polyethylene glycol was added to 45 parts by mass of the solid content of the fine fibrous cellulose dispersion (A) and stirred. Next, an aqueous solution of a polycarbodiimide compound was added so that the amount of the polycarbodiimide compound was 44 parts by mass with respect to 11 parts by mass of polyethylene glycol. The other procedures were the same as in Example 5, and a fine fibrous cellulose-containing sheet was obtained.

[0125] [Example 8] <TEMPO Oxidation> Undried softwood bleached kraft pulp equivalent to 100 parts by mass of dry mass, 1.25 parts by mass of TEMPO (2,2,6,6-tetramethylpiperidine 1-oxyl), and 12.5 parts by mass of sodium bromide were dispersed in 10,000 parts by mass of water. Next, a 13% by mass aqueous solution of sodium hypochlorite was added so that the amount of sodium hypochlorite was 8.0 mmol with respect to 1.0 g of pulp to initiate the reaction. During the reaction, a 0.5 M aqueous solution of sodium hydroxide was added dropwise to maintain the pH at 10 or more and 11 or less, and the reaction was considered to be complete when no change in pH was observed.

[0126] <Washing of TEMPO-Oxidized Pulp> Thereafter, the pulp slurry was dehydrated to obtain a dehydrated sheet, and then 5000 parts by mass of ion-exchanged water was poured, stirred to disperse uniformly, and then filtered and dehydrated to obtain a dehydrated sheet. This process was repeated twice. The amount of substituents (carboxyl groups) introduced was 1.5 mmol / g as measured by titration. The amount of carboxyl groups introduced was measured by treatment with ion-exchange resin and titration using alkali. In the treatment with ion-exchange resin, the fine fibrous cellulose dispersion (A) obtained by mechanical treatment described below was diluted to a concentration of 0.2% by mass, and 1 / 10 by volume of a strongly acidic ion-exchange resin (Organo Corporation, Amberjet 1024: conditioned) was added, and the mixture was shaken for 1 hour. Thereafter, the mixture was poured onto a mesh with an opening of 90 μm, the resin and the dispersion were separated, and the dispersion was subjected to titration using alkali. In the titration using an alkali, the amount of alkali (mmol) required in the first region of the curve shown in Figure 2 (carboxyl group) was divided by the solid content (g) in the slurry to be titrated to obtain the amount of introduced substituent (mmol / g).

[0127] <Mechanical processing> Ion-exchanged water was added to the pulp obtained after washing and dehydration to obtain a pulp dispersion with a solid content concentration of 1.0 mass%. This pulp dispersion was treated with a high-pressure homogenizer (Panda Plus 2000, manufactured by NiroSoavi) to obtain a cellulose dispersion. In the treatment using the high-pressure homogenizer, the mixture was passed through a homogenizing chamber five times at an operating pressure of 1200 bar. Furthermore, this cellulose dispersion was treated with a wet-type micronization device (Ultimizer, manufactured by Sugino Machine Co., Ltd.) to obtain a fine fibrous cellulose dispersion (A). In the treatment using the wet-type micronization device, the mixture was passed through a treatment chamber five times at a pressure of 245 MPa. The average fiber width of the fine fibrous cellulose contained in the fine fibrous cellulose dispersion (A) was 4 nm.

[0128] <Mixing polyol and nitrogen-containing compound> The concentration of the fine fibrous cellulose dispersion (A) was adjusted to 0.5% by mass. Then, to 80 parts by mass of the solid content of the fine fibrous cellulose dispersion (A), a urethane prepolymer aqueous dispersion (Dai-ichi Kogyo Seiyaku Co., Ltd., Elastron H-3-NS, solid content concentration 23.1% by mass) consisting of a polyol-derived unit and a nitrogen-containing compound-derived unit (polyisocyanate-derived unit) was added to 20 parts by mass of the urethane prepolymer and stirred. Next, to 20 parts by mass of the urethane prepolymer, a reaction catalyst aqueous dispersion of an isocyanate group (Dai-ichi Kogyo Seiyaku Co., Ltd., Elastron CAT-21, solid content concentration 13.7% by mass) was added to 0.6 parts by mass of the reaction catalyst and stirred to obtain a fine fibrous cellulose dispersion (B).

[0129] <Sheeting> Next, the finished basis weight of the fine fibrous cellulose-containing sheet (sheet composed of the solid content of the fine fibrous cellulose dispersion (B)) was 50 g / m 2 The fine fibrous cellulose dispersion (B) was weighed out so that the dispersion was 100% by weight, spread on a commercially available acrylic plate, and dried in a thermohygrostat at 35°C and 15% relative humidity. A metal frame for damming (metal frame with inner dimensions of 180mm x 180mm) was placed on the acrylic plate so that the basis weight was the specified. Furthermore, the fine fibrous cellulose-containing sheet formed after drying was peeled off from the acrylic plate and heated at 120°C for 1 hour to promote the reaction between the polyol and the nitrogen-containing compound. A fine fibrous cellulose-containing sheet was obtained by the above procedure.

[0130] Comparative Example 1 The addition of the urethane prepolymer aqueous dispersion and the isocyanate group reaction catalyst aqueous dispersion was omitted in Example 1. The other procedures were the same as in Example 1 to obtain a fine fibrous cellulose-containing sheet.

[0131] Comparative Example 2 The aqueous solution of a polycarbodiimide compound was not added in Example 5. The other procedures were the same as in Example 5 to obtain a fine fibrous cellulose-containing sheet.

[0132] Comparative Example 3 <Polyol Mixing> The concentration of the pulp after washing obtained in <Alkali treatment and washing> of Example 1 was adjusted with ion-exchanged water to a solid content concentration of 15% by mass. Next, 905.3 parts by mass of ion-exchanged water and 28 parts by mass of polyethylene glycol (PEG400, manufactured by Daiichi Kogyo Seiyaku Co., Ltd.) having a molecular weight of 400 as a polyol were added to 28 parts by mass of the solid content derived from the pulp and stirred to obtain a pulp dispersion (A) having a pulp-derived solid content of 2.5% by mass and a polyethylene glycol content of 2.5% by mass.

[0133] <Mechanical processing> The above pulp dispersion (A) was subjected to mechanical treatment in the same manner as in Example 1 to obtain a fine fibrous cellulose dispersion (C). The average fiber width of the fine fibrous cellulose contained in the fine fibrous cellulose dispersion (C) was 80 nm.

[0134] <Mixture of nitrogen-containing compounds> The concentration of the fine fibrous cellulose dispersion (C) was adjusted to 0.5% by mass. Then, an aqueous solution of a polycarbodiimide compound (Nisshinbo Chemical Co., Ltd., Carbodilite V-02-L2, solid concentration 40.1% by mass) was added as a nitrogen-containing compound to 28 parts by mass of polyethylene glycol so that the polycarbodiimide compound was 45 parts by mass, and the mixture was stirred to obtain a fine fibrous cellulose dispersion (D).

[0135] <Sheeting> Next, the finished basis weight of the fine fibrous cellulose-containing sheet (a sheet composed of the solid content of the fine fibrous cellulose dispersion (D)) was 50 g / m 2The fine fibrous cellulose dispersion (D) was weighed out so that the dispersion was 100% by weight, spread on a commercially available acrylic plate, and dried in a thermohygrostat at 35°C and 15% relative humidity. A metal frame for damming (metal frame with inner dimensions of 180mm x 180mm) was placed on the acrylic plate so that the basis weight was the specified. Furthermore, the fine fibrous cellulose-containing sheet formed after drying was peeled off from the acrylic plate and heated at 120°C for 1 hour to promote the reaction between the polyol and the nitrogen-containing compound. A fine fibrous cellulose-containing sheet was obtained by the above procedure.

[0136] (evaluation) The fine fibrous cellulose-containing sheets obtained in the Examples and Comparative Examples were evaluated by the following methods.

[0137] (Total light transmittance) The total light transmittance of the fine fibrous cellulose-containing sheet was measured in accordance with JIS K 7361 using a haze meter (HM-150, manufactured by Murakami Color Research Laboratory).

[0138] (Haze) The haze of the fine fibrous cellulose-containing sheet was measured in accordance with JIS K 7136 using a haze meter (HM-150, manufactured by Murakami Color Research Laboratory).

[0139] (Yellowness before and after heating) The yellowness of the fine fibrous cellulose-containing sheet was measured before and after heating using Colour Cute i (manufactured by Suga Test Instruments Co., Ltd.) in accordance with JIS K 7373. The yellowness after heating was the yellowness of the fine fibrous cellulose-containing sheet vacuum dried at 200°C for 4 hours. The change in yellowness, ΔYI, was calculated from the following formula. ΔYI = (yellowness after heating) - (yellowness before heating)

[0140] (Water absorption rate) The fine fibrous cellulose-containing sheet was cut into 50 mm squares, and conditioned for 24 hours at 23°C and 50% relative humidity, and the conditioned weight was measured. Next, the fine fibrous cellulose-containing sheet after measuring the conditioned weight was immersed in ion-exchanged water for 24 hours, and after wiping off excess water remaining on the surface, the wet weight was measured. From the conditioned weight and wet weight, the water absorption rate (%) of the fine fibrous cellulose-containing sheet was calculated according to the following formula. Water absorption rate (%) = 100 × (wet weight - conditioned weight) / conditioned weight

[0141] (Tensile properties) The tensile modulus and tensile strength of the fine fibrous cellulose-containing sheet were measured using a tensile tester Tensilon (manufactured by A&D Co., Ltd.) in accordance with JIS P 8113. When measuring the tensile modulus and tensile strength, the test pieces were conditioned at 23°C and 50% relative humidity for 24 hours.

[0142] [Table 1]

[0143] As is clear from Table 1, in Examples 1 to 8, which contain a polymer containing a unit derived from a polyol and a unit derived from a nitrogen-containing compound, a fine fibrous cellulose-containing sheet having high transparency, low water absorption, and high tensile modulus was obtained. In Comparative Example 1, which does not contain a polymer containing a unit derived from a polyol and a unit derived from a nitrogen-containing compound, and Comparative Example 2, which does not contain a unit derived from a nitrogen-containing compound, the water absorption was high, and practical problems were concerned from the viewpoint of water resistance. In Comparative Example 3, in which a polyol was mixed before mechanical treatment, a fine fibrous cellulose-containing sheet having low water absorption was obtained, but the transparency was not sufficiently improved due to the large fiber diameter of the fine fibrous cellulose, suggesting that applicable uses are limited.

Claims

1. Fibrous cellulose having a phosphate group or a substituent derived from a phosphate group; A polymer including a unit derived from a polyol and a unit derived from a nitrogen-containing compound, The average fiber width of the fibrous cellulose is 2 nm or more and 50 nm or less, the unit derived from a nitrogen-containing compound is a unit derived from at least one compound selected from an isocyanate compound and a carbodiimide compound, The haze of the sheet is 30% or less; The sheet has a tensile modulus of 4.0 GPa or more.

2. 2. The sheet according to claim 1, which has a water absorption rate of 5000% or less.

3. 3. The sheet according to claim 1, which has a total light transmittance of 86% or more.

4. The sheet according to any one of claims 1 to 3, wherein the unit derived from a polyol is a unit derived from a diol.

5. The yellowness of the sheet measured in accordance with JIS K 7373 is expressed as YI 1 The sheet was dried in a vacuum at 200° C. for 4 hours, and the yellowness index was determined as YI. 2 In this case, YI 2 -YI 1 The sheet according to any one of claims 1 to 4, wherein the value of is 50 or less.

6. The sheet according to any one of claims 1 to 5, wherein the content of the polymer containing a unit derived from a polyol and a unit derived from a nitrogen-containing compound is 15% by mass or more and 85% by mass or less with respect to the total mass of the sheet.

Citation Information

Patent Citations

  • Coating agent and molded product

    JP2010184999A

  • Fiber strengthening transparent resin composition, method of manufacturing the same, and transparent sheet

    JP2012025833A

  • Polyurethane resin composition

    JP2013194162A

  • Resin composition, resin molded article and production method of the same

    JP2017141394A

  • Transparent base and method for producing same

    WO2012032931A1